Prevalence of somatic diseases in adults with attention deficit hyperactivity disorder in Japan is highest in people aged ≥40 years with mental disorders: a cross-sectional study of a Japanese health insurance claims database - Takaesu, Yoshikazu; Sato, Yumi; Iwata, Shinpei; Takizawa, Patcharapim; Miyauchi, Hideyuki; Ishimoto, Yoshikazu; Kondo, Tsuyoshi (Frontiers in Psychiatry, 2024)
Introduction Studies have reported an association between attention deficit hyperactivity disorder (ADHD) and somatic diseases; however, the correlation of mental disorders with the association between ADHD and somatic diseases remains uninvestigated. This study investigated and compared the prevalence of somatic diseases among adults with/without ADHD, stratified by the presence or absence of mental disorders. Methods This cross-sectional study (October 2020–September 2021), using data (June 2013–September 2021) from a Japanese health insurance claims database, included adult participants with a medical record of and receiving medication for ADHD (ADHD group); the control group (matched 1:5 by age/sex) comprised participants without ADHD. The prevalence and odds ratio (OR; ADHD versus control) of type 2 diabetes mellitus (T2DM), diabetes complications, hypertension, cardiovascular disease (CVD), dyslipidemia, gout and hyperuricemia, chronic obstructive pulmonary disease (COPD), non-alcoholic fatty liver disease/non-alcoholic steatohepatitis (NAFLD/NASH), and atopic dermatitis were investigated. Pooled ORs for stratified analysis were calculated using the Mantel-Haenszel method. Results In the matched analysis sets, the ORs for all somatic diseases were significantly higher for the ADHD group (n=15,028) versus the control group (n=74,796). On stratified analysis, the Mantel-Haenszel ORs were significant for NAFLD/NASH (1.53; 95% confidence interval [CI]: 1.34, 1.73), diabetes complications (1.39; 95% CI: 1.09, 1.77), and gout and hyperuricemia (1.34; 95% CI: 1.19, 1.51). Furthermore, the stratum-specific ORs for T2DM, hypertension, and dyslipidemia were >1 and <1 in the presence and absence of mental disorders, respectively. The prevalence of all somatic diseases except atopic dermatitis increased with age. For participants aged ≥40 years, the Mantel-Haenszel ORs were significant for all somatic diseases except CVD, COPD, and atopic dermatitis. Conclusions The prevalence of several somatic diseases, including chronic disorders, was high among adults with ADHD, particularly in those aged ≥40 years and those with mental disorders.